Emotional profile and the mathematical competences of the future primary school teachers - Rafael Escolano Vizcassa; José María Gairín Sallén; Clara Giménez-Gestal; Jesús Murillo Ramón; Luz Roncal Gómez (Universidad de La Rioja, 2013)
The global aim of this research is to continue the work, carried out for more than ten years (Hidalgo, Maroto y Palacios, 1999 e Hidalgo, 107 Contextos Educ., 15 (2012), 107-134 CONTEXTOS EDUCATIVOS, 15 (2012), 107-134 Maroto, Ortega y Palacios, 2008), focused on the analysis of the factors involved in the student's performance concerning the mathematics subject. We try now to complete the study, in the different educational levels, that we started with the Childhood and Primary Education, and we analyze the universitary level and the mathematics teachers-to-be. In this paper, we show the first results that allow us to consider the relationship between the emotional profile of the future Primary School teachers and their beliefs about their work as mathematics teachers. In the first part of the paper, we investigate the mathematical competence of firstyear students in four Spanish universities, using two questionnaires made up with the released tests of PISA Report 2003. In the second part of the paper, we study the relations between the mathematical competence of the future teachers, their beliefs about the nature of mathematics and their beliefs about their competence as mathematics teachers, by using some scales developed and validated in previous I+D projects.